A Study to Assess the Effect of Distraction Using Rattle on Pain among Infants during IV Cannulation - Gayathri, R. (Indian Journal of Nursing Sciences, 2024)
Pain is a subjective experience and children respond to pain with behavior that depends on their age and cognitive process. The aim of this study was to assess the effect of distraction using rattle on pain among infants during IV Cannulation in Upasana Hospital, Kollam. Quantitative research approach was adopted for this study. Quasi-experimental post-test only control group design and purposive sampling technique was used to select 40 infants aged between 2 and 6 months, 20 each in the experimental group and control group at Upasana Hospital, Kollam. After obtaining consent from the concerned authorities of the hospital and participants caregiver, the study was done. Distraction using rattle provided to the experimental group for few minute during beginning to till end of the procedure. No intervention was given in the control group. Pain assessment was done by Neonatal Infant Pain Scale during procedure. The data thus collected were analyzed using differential and inferential statistics. Analysis revealed that the mean pain score of control group (5.3) was significantly higher than the mean pain score of experimental group (2.4) and calculated “t” value (6.74) was greater than table value (1.69) at 0.05 level of significance. There was significant association between the pain score among infants with selected demographic variables such as age in month, birth order, weight of child in experimental group and age in month, and site of cannulation in control group. Therefore, it is interpreted that the distraction using rattle among infants during IV cannulation is effective in reducing the pain.